The twilight of constitutionalism? - Loughlin, Martin; Dobner, Petra (Oxford : Oxford University Press, 2010)
The essays gathered in this collection explore the effects of recent changes on two of the main building blocks of constitutionalism, statehood and democracy. It also looks at movements to overcome statehood in the EU and considers possible transformations to, or substitutes for statehood.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constituent power; Legitimacy of governments; International organization